Twenty years of management of care in Chile: what we know, what we do not know, what is yet to come. An analysis of arguments. Issue 3 (16th July 2018) - Ayala, Ricardo A
Abstract : For over 20 years, the notion of 'management of care' has been foregrounded as key in the jurisdiction of the nursing profession, with the aim of detaching itself from the wider medical umbrella. A number of voices have advocated such centrality. These include juridical, academic and occupational perspectives. Critical stances, although peripheral, have also been voiced. These have been received, at best, with a 'polite silence' in mainstream circles. By looking at the arguments surrounding the 'management of care' circulated in these two decades, this article reports the various forms of discursive practice that participate in the political process of autonomy building. Particularly, we focus on the validity of the arguments as well as the cohesion across arguments within the knowledge system. In doing so, we evaluate its main premises and foundations, the reach of the conceptualisation and its disjointed, differing and incomplete bases. Similarly, we used an inferential technique for the reconstruction of omitted and unexpressed assertions. The article introduces an approach of the humanities that is seldom seen in healthcare. It also proposes a research agenda in regard to management of care for the upcoming decades.